POLITICAL COMMUNICATION OF LEGISLATIVE CANDIDATES IN THE 2024 ELECTION IN TANAH BARU VILLAGE PAKISJAYA DISTRICT KARAWANG REGENCY - Ariyanto, Bagas (Universitas Teuku Umar, 2024)
In a situation full of political dynamics and tight competition in the General Election, having a mature communication strategy is crucial for every legislative candidate who wants to gain public support effectively. Political communication is one of the most crucial aspects in the legislative election, especially at the local level. At the local level, political communication functions as a bridge between prospective leaders or policy makers and the local community. Although social relations in the village community are running well, in the political realm there are often clashes and conflicts. This study aims to analyze the political communication strategies used by legislative candidates in Tanah Baru Village, Pakisjaya District, Karawang Regency, in the 2024 General Election. The main focus of this study is to understand how legislative candidates formulate and implement their communication strategies in a local context. This study uses qualitative descriptive with a constructivist perspective and a case study approach. The results of the study show that the political communication strategy of legislative candidates in the 2024 Election uses a holistic approach that combines strategies for providing educational scholarships and building rice field irrigation infrastructure. Other political communication strategies are carried out with a personal approach through blusukan campaigns and campaigns on social and conventional media, which effectively obtained the second most votes out of the five other legislative candidates running in one party